More on Montale’s "Midsummer-Night’s Dream" translations. New witnesses and documents (Prassi Ecdotiche della Modernità Letteraria, 2024)
The essay presents a new witness to Montale’s Midsummer-Night’s Dream translation. It consists of the script owned by Guido Salvini, who collaborated with Max Reinhardt in directing the show during the Maggio Musicale Fiorentino in 1933. This script contains the first form of the translation, earlier to the text used by Reinhardt (worse, as the new witness helps to show) and to the booklet (which contains, as is known, a text partially modified by Francesco Pastonchi). The script is also compared with a copy of the booklet that Montale gave to Mario Praz: Montale’s annotations on this copy confirm his primitive metrics and translation choices. Lastly the full text of Montale’s translation according to the Salvini-script is published, together with the booklet variants and Montale’s annotations.
Keywords: Eugenio Montale; William Shakespeare; Guido Salvini; Max Reinhardt; Francesco Pastonchi; Mario Praz; Maggio Musicale Fiorentino; Midsummer-Night’s Dream; Quaderno di traduzioni; manuscript; variants